А Prevalence survey of parasitic helminths of cashmere goats in Bayankhongor province, Mongolia (Mongolian Journal of Agricultural Sciences, 2020)
Infections with gastrointestinal parasites can negatively affect the health and the overall productivity of infected animals. The aim of the present study was to determine the prevalence of gastrointestinal parasite infections in cashmere goats in Bayankhongor province, Mongolia. Faeces samples (n = 614) were collected from two sums (Bogd and Bombogor) in Bayankhongor province, Mongolia from July to September 2018 and examined by flotation methods. Positive samples were examined by the modified McMaster technique to determine the parasitic load. The overall prevalence of helminths infections was 44% followed by Strongylids (42.6%), Nematodirus. (36.4%), Moniezia spp. (4.8%), Concurrent infection with two or more species was common, with mixed infection observed in 26% of goats.Баянхонгор аймгийн зарим сумдын ноолуурын үүлдрийн ямааны баасанд гельминтийн өндөг илрүүлсэн дүнгээсБаянхонгор аймгийн Богд, Бөмбөгөр сумдад үржүүлж буй ноолуурын үүлдрийн Залаа жинстийн цагаан,Бөмбөгөрийн Улаан ямаанд түүвэрлэлтийн аргаар сонгон авсан нийт 614 ямааны баасны дээжинд Nematodirus (36.4%), Moneiza (4.8%) ,Strongylus (42.6%) төрлийн гельминтийн өндөг  илрэв.Түлхүүр үг: ямааны үүлдэр, strongylus, nematodirus, monieza